2001
DOI: 10.1200/jco.2001.19.18.3861
|View full text |Cite
|
Sign up to set email alerts
|

Primary Gastrointestinal Non-Hodgkin’s Lymphoma: I. Anatomic and Histologic Distribution, Clinical Features, and Survival Data of 371 Patients Registered in the German Multicenter Study GIT NHL 01/92

Abstract: PGI NHL are heterogeneous diseases. The number of localized PGL allowed for detailed analyses. Larger studies are needed for stages III and IV and for intestinal NHL. A uniform reporting system for PGI NHL, in terms of definitions and histologic and staging classifications, is needed to facilitate comparison of treatment results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

32
288
9
28

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 425 publications
(357 citation statements)
references
References 33 publications
32
288
9
28
Order By: Relevance
“…Similar results were reported by Ruskoné-Fourmestraux et al 18 and Koch et al 25 The poor prognosis of the combined group in our study may have been associated with more frequent T-cell phenotype and more advanced-stage disease. In three studies, 18,23,25 however, T-cell lymphomas were extremely rare. This discrepancy may correlate with the difference in the incidence of T-cell lymphoma between Western countries and Japan.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Similar results were reported by Ruskoné-Fourmestraux et al 18 and Koch et al 25 The poor prognosis of the combined group in our study may have been associated with more frequent T-cell phenotype and more advanced-stage disease. In three studies, 18,23,25 however, T-cell lymphomas were extremely rare. This discrepancy may correlate with the difference in the incidence of T-cell lymphoma between Western countries and Japan.…”
Section: Discussionsupporting
confidence: 93%
“…In our series, the gastric group comprised 75% of all patients. This percentage was similar to that in studies from Austria 17 and Germany 25 and the value is higher than that observed in NS: not significant. a P Ͻ 0.006 is significant using the Bonferroni correction.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…20 The overall incidence of EMZL in the intestine is quite low and accounts for only about 2.7% of all cases of gastrointestinal non-Hodgkin lymphomas. 21 Primary colorectal lymphoma accounts for only about 0.2% of large intestinal malignancies. 22 Moreover, colorectal EMZLs differ from gastric variants not only in terms of the etiologic infectious organism but also in terms of its clinical presentation and treatment.…”
Section: Discussionmentioning
confidence: 99%